Packing coefficient determining the packing density difference of CHON-containing isomers - Yao-yao Linghu; Chao-yang Zhang (Energetic Materials Frontiers)
Packing density is a basic property of substances and acts as one of important decisive factors of service performances. This work focuses upon the determining factors of packing density at the premise of CHON-containing isomers with the same chemical composition. It is found that, for a group of CHON-containing isomers, the molecular densities vary much less than the packing coefficients and packing densities, regardless a significant difference of molecular structure therein. Thus, packing coefficient governs packing density, and strategy based on data analysis for elevating it is proposed, such as the introduction of strong and dense hydrogen bonds and the formation of internal salt. Additionally, C=O is beneficial for increasing packing density while reducing energy release, and thus can hardly be considered in energetics. Hopefully, this work will deepen the understanding of packing density and offer a new avenue for designing high energy compounds.